ASAS PENGAYOMAN DALAM SISTEM JAMINAN PRODUK HALAL DI KABUPATEN ACEH BARAT - Yuana, Adella; Sandela, Ilka; Trisna, Nila (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
Aceh Qanun No. 8/2016 on Halal Product Guarantee System is based on the principle of protection. The principle of protection is a function of the Government of Aceh to protect the lives of all people, not only Muslims, but all other religious communities. In this case, the Government of Aceh tries to provide a guarantee of legal certainty for products consumed by the community. Based on the data found, there are 94 MSMEs in West Aceh Regency, but only 30 MSMEs have halal certificates. Based on this, there are two problems, namely the implementation of the principle of protection in the halal product guarantee system and how the form of Local Government supervision of the halal product guarantee system in West Aceh Regency. The research method used is empirical juridical which produces descriptive data regarding the Principle of Protection in the Halal Product Guarantee System in West Aceh Regency. The result of the research found that the implementation of the principle of penayoman by the Government of Aceh to provide legal certainty guarantees for products consumed by the public has not been maximized. This can be seen from the number of Micro, Small and Medium Enterprises that do not have halal certificates that are still many. The application of the principle of protection that has not been maximised is also influenced by the supervision system that has not been maximised either. Supervision involves several institutions in the West Aceh District Government such as the Ministry of Religion and the Health Office. The main obstacle that occurs is the lack of funds allocated for this limited supervision so the supervision of halal products for Micro, Small and Medium Enterprises in West Aceh is not optimal